Heat-waves and mortality in Czech cities: a case study for the summers of 2015 and 2016 - Arsenovic, Daniela; Lehnert, Michal; Fiedor, David; Šimáček, Petr; Středová, Hana; Středa, Tomáš; Savić, Stevan (Geographica Pannonica, 2019)
The aim of this paper was to assess the impact of heat-waves on mortality in ten Czech cities, using data recorded during the summers of 2015 and 2016. Temperature-related mortality during heat-waves was investigated by comparing mortality figures on heat-wave days and those on other days by means of the Mann-Whitney U test. Results for all-cause mortality, cardiovascular and respiratory diseases (CVD+R) mortality, as well as for mortality in the over-65 age group, show statistically significant differences (p